Mechanical and Thermal Properties of PLA Biocomposites Reinforced by Coir Fibers. (10th July 2017) - Sun, Zhihui; Zhang, Li; Liang, Duoping; Xiao, Wei; Lin, Jing
Abstract : In this work, polylactic acid (PLA) biocomposites reinforced with short coir fibers were fabricated using a corotating twin-screw extruder and injection molding machine. Short coir fibers were treated by mixed solution including hydrogen peroxide and sodium hydroxide to improve the adhesion between fibers and PLA matrix. The effects of treated coir fiber content (1, 3, 5, and 7 wt%) on tensile, impact, thermal properties, and surface morphology of PLA biocomposites were investigated. The best impact strength results were obtained for 3 wt% PLA/treated coir fiber biocomposites, where the impact strength was increased by approximately 28% compared to the neat PLA. The tensile modulus of PLA biocomposites was increased by increasing the treated coir fiber content. These results were confirmed by morphological structure analysis. Differential scanning calorimetry (DSC) results demonstrated a minor effect of the treated coir fiber on thermal behavior of PLA resin. Thermogravimetry analysis (TGA) demonstrated that the thermal stability of the PLA/treated coir fiber biocomposites was reduced by the incorporation of treated coir fiber.